Evaluating the Impact of Egyptian Social Fund for Development Programs - Abou-Ali, Hala (2012)
The Egyptian Social Fund for Development was established in 1991 with a mandate to reduce poverty. Since its inception, it has disbursed about $2.5 billion, of which nearly two-fifths was devoted to supporting microcredit and financing community development and infrastructure. This paper investigates the size of the impact of the Fund s interventions, whether the benefits have been commensurate with the costs, and whether the programs have been targeted successfully to the poor. The core of the impact evaluation applies propensity-score matching to data from the 2004/2005 national Household Income, Expenditure and Consumption Survey. The authors find that Egypt s Social Fund for Development programs have had clear and measurable effects, in the expected direction, for all of the programs considered: educational interventions have reduced illiteracy, health and potable water programs have lowered household spending on health, sanitation interventions have cut household spending on sanitation and lowered poverty, and road projects have reduced household transportation costs by 20 percent. Microcredit is associated with higher household expenditures in metropolitan areas and urban Upper Egypt, but not elsewhere. The Social Fund for Development s road projects generate benefits that, by some estimates, exceed the costs, as do health and potable water interventions; this is less evident for interventions in education and sanitation. The Fund argues that its mission is primarily social, and so should not be judged using a cost-benefit analysis. The Fund support for microcredit is strongly pro-poor; the other programs analyzed have a more modest pro-poor orientation.